The Relationship Between Family Support and Anxiety in Trimester III Pregnant Women Facing Childbirth at Dr. Sobirin Regional Hospital Musi Rawas Regency 2025 - Yumi Yanti; Bella Anarkie; Meita Tria Saputri (Student Scientific Journal, 2026)
According to global data from the World Health Organization (WHO), worldwide, approximately 10% of pregnant women and 13% of new mothers experience mental disorders, particularly depression. In developing countries, this figure is even higher, at 15.6% during pregnancy and 19.8% after childbirth. In severe cases, maternal distress can be so severe that they may even commit suicide. Furthermore, affected mothers are unable to function properly. As a result, child growth and development can also be impaired (WHO, 2023). The purpose of this study was to determine the relationship between family support and anxiety in third-trimester pregnant women facing childbirth at Dr. Sobirin Regional Hospital, Musi Rawas Regency in 2025.The study used a cross-sectional design. Data were collected by distributing questionnaires to 33 respondents, including pregnant women in their third trimester at Dr. Sobirin Regional Hospital, Musi Rawas Regency, using a total sampling technique. Univariate analysis revealed that more than half of the respondents, or 54.5%, were in the third trimester of pregnancy. Musi Rawas Regency in 2025 experienced poor family support, and more than half of respondents, or 57.6%, of third-trimester pregnant women, experienced high levels of anxiety during childbirth at Dr. Sobirin Regional General Hospital (RSUD) in Musi Rawas Regency in 2025. Bivariate analysis revealed a significant relationship between family support and third-trimester anxiety levels during childbirth at Dr. Sobirin Regional General Hospital (RSUD) in Musi Rawas Regency in 2025, with a p-value of 0.003.Dr. Sobirin Regional General Hospital (RSUD) in Musi Rawas Regency and related institutions should improve antenatal care services that focus not only on the physical aspects but also on the psychological aspects of pregnant women.